Long-Term Residential Care Worker Mental Health: The Power of Public Recognition During the COVID-19 Pandemic - Sofia Celis; Nick Boettcher; Bonnie Lashewicz (Journal of Long-Term Care)
Context: Facing unprecedented barriers to providing adequate care, along with a lack of recognition from the public, long-term residential care (LTRC) workers were at risk for mental health concerns, particularly moral distress, during the COVID-19 pandemic.